1990
DOI: 10.1523/jneurosci.10-01-00267.1990
|View full text |Cite
|
Sign up to set email alerts
|

Altered patterns of dynorphin immunoreactivity suggest mossy fiber reorganization in human hippocampal epilepsy

Abstract: Dynorphin A(1-17), an opioid peptide that is normally present in the hippocampal mossy fiber system, was localized immunocytochemically in the hippocampal formation of control autopsy and temporal lobe epilepsy (TLE) specimens. In control tissue, dynorphin-like immunoreactive (Dyn-IR) structures were confined to the mossy fiber path and were most highly concentrated in the polymorph (hilar) region of the dentate gyrus. Very few Dyn-IR structures were present in the molecular and granule cell layers of the dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
304
1
10

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 568 publications
(336 citation statements)
references
References 47 publications
21
304
1
10
Order By: Relevance
“…Similar to other species, dynorphin marks the terminal fields of the dentate granule cells in the hilus and mossy fiber zone of the hippocampus (Drake et al, 1994;Khachaturian et al, 1982). The staining pattern in the polymorphic cell layer corresponds to that seen in the human hippocampus (Houser et al, 1990).…”
Section: Gap-43supporting
confidence: 61%
“…Similar to other species, dynorphin marks the terminal fields of the dentate granule cells in the hilus and mossy fiber zone of the hippocampus (Drake et al, 1994;Khachaturian et al, 1982). The staining pattern in the polymorphic cell layer corresponds to that seen in the human hippocampus (Houser et al, 1990).…”
Section: Gap-43supporting
confidence: 61%
“…Selective effects of NR2A and NR2B antagonists on mossy fiber sprouting Activation of NMDARs has been implicated in seizure-induced mossy fiber sprouting, which is also a feature of human limbic epilepsy (Sutula et al, 1989;Houser et al, 1990;Sutula et al, 1996). It is thus of interest to determine whether the selective impediment of epileptogenesis by NR2A antagonist is also reflected in seizure-induced mossy fiber sprouting, which normally occurs a few weeks after SE.…”
Section: Effects Of Nr2a and Nr2b Antagonists On Se-induced Neuronal mentioning
confidence: 99%
“…[10][11][12] More recent work has shed light on the basic physiopathological mechanisms responsible for mesio-temporal epilepsy. [13][14][15][16][17][18][19][20] Studies on mesio-temporal kindling have brought further ABSTRACT: Numerous studies of the electrophysiology and neuropathology of temporal lobe epilepsy have demonstrated the mesial temporal structures to be the site of seizure origin in the majority of cases. This is the rationale for a transcortical selective approach, first introduced by Niemeyer, for removal of the hippocampus and amygdala.…”
Section: Suppl 1 -S68mentioning
confidence: 99%